Penerapan Pengendalian dengan Agens Hayati Lokal untuk Solusi Permasalahan Serangan OPT pada Tanaman Padi Organik di Desa Bumi Agung, Tegineneng, Pesawaran: Application of Control with Local Biological Agents to Solve OPT-Attack Problems on Organic Rice Plants in Bumi Agung Village, Tegineneng, Pesawaran - Lina Budiarti; Ni Siluh Putu Nuryanti; Dulbari Dulbari; Yuriansyah Yuriansyah; Priyadi Priyadi; Rizky Rahmadi; Fajar Rochman; Denny Sudrajat; Evi Yunita Sari; Dewi Ermaya (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
OPT problems are still a major obstacle to organic rice cultivation due to limited understanding and control skills. The aim of implementing community service activities is to provide additional skills and insight regarding OPT control technology with local biological agents to solve the problem of organic rice farming in Bumiagung village, Tegineneng, Pesawaran. Technology transfer activities regarding the application of control with local biological agents to solve the problem of pest attacks on organic rice plants were carried out in Bumiagung Village, Tegineneng, Pesawaran which were carried out in June - October 2022 to the Progressive Organic Farmers Community. The stages of the activity are carried out in stages through conducting surveys, providing material, pre-testing, training and mentoring, post-testing, monitoring, and evaluation at the end of the activity. Before the activity begins, a survey is carried out to analyze conditions and problems and analyze the solutions needed for these problems. Farmers need to gain more knowledge and skills in managing pests that attack their land. The controls that are often used are vegetable pesticides and refugia. From the final evaluation results, the analysis shows that farmers realize that control with biological agents is effortless, inexpensive, and synergistic in supporting organic farming.